Odwieczność - okiem przyrodnika czyli meandry filogenezy świata zwierząt - Blaszak, Czesław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
In the present review, an attempt to define the animal kingdom against a background of other kingdoms in the domain of eukaryotic organisms is presented,showing the common features linking the animal kingdom with the kingdom of fungi.The animals were clearly separated from other kingdoms through two unique systemscharacteristic of them: nervous and muscular. The matter is complicated by the fact that in the four types of the animal kingdom (Porifera, Placozoa) the nervous and muscular systems are absent. Therefore, zoologists proposed the name Metazoa multicellularanimal – for the animal kingdom. The main problematic issues of monophyly based onselected phylogenetic groups and phyla are discussed. In addition to the phylogenetictree (based on monophyly) the punctuated equilibrium was established for four independentgroups: Porifera, Cnidaria, Protostomia, Deuterostomia. Finally, the position ofthe animal kingdom in the monophyletic point of view and against a background of all other organisms is presented.